PEMBANGUNAN PERUMAHAN PADA AREAL SITUS BITING, LUMAJANG - Muhammad Hidayat (Berkala Arkeologi, 1996)
Cases on Biting Sites may occur because the site has not been legally designated as a Cultural Conservation Area and has not been properly managed. To avoid cases such as on Biting Sites, it is time for important sites in Indonesia to be legally designated as Cultural Conservation Areas, and their preservation and utilization are managed according to their potential.